2011
DOI: 10.1111/j.1757-1707.2010.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of bird and mammal response to short-rotation woody crops

Abstract: Short-rotation woody cropping (SRWC) refers to silvicultural systems designed to produce woody biomass using short harvest cycles (1-15 years), intensive silvicultural techniques, high-yielding varieties, and often coppice regeneration. Recent emphasis on alternatives to fossil fuels has spurred interest in producing SRWC on privately owned and intensively managed forests of North America. We examined potential bird and small mammal response at the stand level to conversion of existing, intensively managed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 30 publications
1
53
0
3
Order By: Relevance
“…Riffell et al [61] recently reviewed literature related to biodiversity and SRWCs in the U.S. and conducted a meta-analysis of bird and small mammal responses where sufficient data permitted. They characterized their findings as -tentative‖ due to the small number of studies; seven studies had data sufficient to allow meta-analysis of bird responses and only two studies provided enough information to allow meta-analysis of small mammal responses.…”
Section: Biological Diversitymentioning
confidence: 99%
“…Riffell et al [61] recently reviewed literature related to biodiversity and SRWCs in the U.S. and conducted a meta-analysis of bird and small mammal responses where sufficient data permitted. They characterized their findings as -tentative‖ due to the small number of studies; seven studies had data sufficient to allow meta-analysis of bird responses and only two studies provided enough information to allow meta-analysis of small mammal responses.…”
Section: Biological Diversitymentioning
confidence: 99%
“…A meta-analysis recently conducted in the United States found that Populus based short rotation forestry stands generally harbored lower levels of avian diversity than reference woodlands, but none of the studies directly compared short rotations stands with forest plantations (Riffell et al 2011). Likewise, comparisons of the biodiversity in short rotation production forests with broadleaves and more conventional conifer dominated production forests are largely lacking in Northern Europe.…”
Section: Bird Species Richness and Abundancementioning
confidence: 99%
“…or eucalyptus (Eucalyptus spp.) [6,7]. However, more recent efforts also have examined whether perennial grasses such as switchgrass (Panicum virgatum), a species native to eastern North America, could be intercropped between rows of crop trees in pine (Pinus spp.)…”
Section: Introductionmentioning
confidence: 99%